Protective Effects of Gallic Acid and Curcumin on Serum Levels of Hepatic Transaminases, Blood Plasma Parameters and Pituitary-testicular Hormones in Rats Treated Nickel Nanoparticles - Rahimeh Khezri Motlagh; Akbar Vahdati; Seyed Ebrahim Hosseini; Mohammad Amin Edalatmanesh (Jurnal Ilmu Ternak dan Veteriner, 2022)
Nickel nanoparticles (NiNPs) have toxic effects on body cells due to the production of free radicals. The purpose of this research was to investigate the protective effects of Gallic acid (GA) and Curcumin (Cur) on hepatic transaminases, blood plasma parameters and pituitary-testicular hormones levels in NiNPs-treated rats. Seventy adult male Wistar rats were divided in 7 groups of 10 including control, Ni50 mg/kg, Ni50+GA150 mg/kg, Ni50+GA300 mg/kg, Ni50+Cur150 mg/kg, Ni50+Cur300 mg/kg and Ni50+GA300+CUR300 mg/kg. NiNPs, GA and Cur were administered orally by oral gavage for 28 days. At the last phase of the study, the samples of blood were taken directly from heart and serum levels of hepatic transaminases (alanine aminotransferase (ALT) and aspartate aminotransferase (AST)), blood plasma parameters (Glucose, total protein (TP), bilirubin (Bil), albumin (Alb), creatinine (Cr), Blood urea nitrogen (BUN), triglyceride, cholesterol, HDL, LDL and alkaline phosphatase (ALP)) and pituitary-testicular hormones (FSH, LH, testosterone and dihydrotestosterone) were assessed. NiNPs administration increased serum levels of glucose, ALT, ALP, AST, Bil, BUN, Cr, triglyceride, cholesterol and LDL compared to the control group (p0.05) and in contrast, it decreased serum levels of FSH, LH, testosterone, dihydrotestosterone, Alb, TP and HDL (p0.05). However, co-administration of GA and Cur at doses of 300 ml/kg in NiNPs -treated rats improved all blood plasma parameters compared to the control group (p0.05). The findings of this study suggest that co-administration of GA and Cur at a dose of 300 mg/kg can reduce and improve the damaging effects of NiNPs on blood plasma parameters, hepatic transaminases and pituitary-testicular hormones in adult rats.